2015
DOI: 10.1093/cs/cdv024
|View full text |Cite
|
Sign up to set email alerts
|

Children's Experiences of Cyberbullying: A Canadian National Study

Abstract: How to cite TSpace items Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the TSpace version (original manuscript or accepted manuscript) because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 28 publications
3
31
0
1
Order By: Relevance
“…In this sense, it has been found that teenagers who use the Internet for more hours a day are more likely to be cyber-aggressors (Festl et al, 2015;Mishna et al, 2012;Rice et al, 2015) and, specifically, that the frequency of online communication and use of social networks is a risk factor for cyberaggression (Lee & Shin, 2017;Sticca, Ruggieri, Alsaker, & Perren, 2013). Having been a victim of cyber-aggression increases the probability of becoming a cyber-aggressor as well (Beran, Mishna, McInroy, & Shariff, 2015;Festl et al, 2015;Kowalski, Giumetti, Schroeder, & Lattanner, 2014).…”
Section: Predictores Individuales Familiares Y Comunitarios De La CImentioning
confidence: 99%
“…In this sense, it has been found that teenagers who use the Internet for more hours a day are more likely to be cyber-aggressors (Festl et al, 2015;Mishna et al, 2012;Rice et al, 2015) and, specifically, that the frequency of online communication and use of social networks is a risk factor for cyberaggression (Lee & Shin, 2017;Sticca, Ruggieri, Alsaker, & Perren, 2013). Having been a victim of cyber-aggression increases the probability of becoming a cyber-aggressor as well (Beran, Mishna, McInroy, & Shariff, 2015;Festl et al, 2015;Kowalski, Giumetti, Schroeder, & Lattanner, 2014).…”
Section: Predictores Individuales Familiares Y Comunitarios De La CImentioning
confidence: 99%
“…Cyberbullying has been the predominant term used by Canadian (and other) researchers to refer to online behaviors that are offensive, derogatory, exclusionary, unwanted, and hurtful (Beran et al 2015;Cassidy et al 2013;Deschamps and McNutt 2016;Li 2010;Mishna et al 2014), and self-reports have been the primary means through which researchers have been able to learn about this problem (Beran et al 2015;Cassidy et al 2009;Li 2010;Mishna et al 2012). Specific operational definitions of cyberbullying vary and no universal tool for measuring cyberbullying prevalence has been adopted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, prevalence rates vary. For example, several Canadian studies report cyberbullying victimization rates ranging from 14% to 50% of youth surveyed and self-reported cyberbullying perpetration rates ranging from 25% to 36% (Beran et al 2015;Cassidy et al 2009;Cénat et al 2015;Li 2010;Mishna et al 2010Mishna et al , 2012Wade and Beran 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Por sua vez, diferenças entre os sexos ainda não estão bem estabelecidas. Enquanto algumas pesquisas não encontraram diferenças em relação a sexo (Beran et al, 2015;Smith et al, 2008), outras indicam que meninas tendem a estar mais envolvidas do que meninos (Beckman, Hagquist, & Hellström, 2013;Calvete, Orue, & Gámez-Guadix, 2015;Smith et al, 2008).…”
unclassified